PTU-042 Appropriately Trained Registrars Are As Good As Consultants In Endoscopic Management Of Moderate-severe Upper Gastrointestinal Haemorrhage. (9th June 2014) - McShane, M; Hewett, R; Sadler, G; Poullis, A
Abstract : Introduction: The South West Thames region operates a unique regional gastrointestinal service covering 4 hospitals. Registrar endoscopists are assessed and signed off as competent in providing endoscopic haemostatic therapy before taking their place on the GI bleed rota, and are supported by an on-call consultant. We aimed to evaluate if there were any operator-dependent differences in outcomes of endoscopic procedures performed in cases of moderate-severe upper gastrointestinal haemorrhage between consultants and registrars Methods: Data were recorded for all emergency OGDs performed at St. George's Hospital, between 01/01/13 and 30/06/13, in patients presenting with haematemesis or melaena and requiring endoscopy. The Rockall score for each patient was calculated and plotted against mortality for the whole population, and then sub classified into consultant- or registrar-performed procedures. Results: 110 procedures performed on 101 patients (41 female, 60 male, median age 71, age range 23–93, and an overall mortality of 29.7%) were analysed A direct relationship between an increasing Rockall score and mortality was demonstrated in both the overall population, and also in the registrar-performed procedures, inferring typical population characteristics. Mortality for registrar-performed procedures showed no appreciable difference to that of the overall patient population. Conclusion: Descriptors for achieving competence in therapeutic endoscopy have yet to be defined by the JAG. However, provided local mechanisms for delivering training in, and assessment of, competence at providing endoscopic haemostatic therapy are robust, our findings support the use of a registrar-led out-of-hours GI bleed service. Disclosure of Interest: None Declared.